Role of epithelial sodium channel-related inflammation in human diseases - Chen, Yabin; Yu, Xiao; Yan, Zhiping; Zhang, Shuijun; Zhang, Jiacheng; Guo, Wenzhi (Frontiers in Immunology, 2023)
The epithelial sodium channel (ENaC) is a heterotrimer and is widely distributed throughout the kidneys, blood vessels, lungs, colons, and many other organs. The basic role of the ENaC is to mediate the entry of Na+ into cells; the ENaC also has an important regulatory function in blood pressure, airway surface liquid (ASL), and endothelial cell function. Aldosterone, serum/glucocorticoid kinase 1 (SGK1), shear stress, and posttranslational modifications can regulate the activity of the ENaC; some ion channels also interact with the ENaC. In recent years, it has been found that the ENaC can lead to immune cell activation, endothelial cell dysfunction, aggravated inflammation involved in high salt-induced hypertension, cystic fibrosis, pseudohypoaldosteronism (PHA), and tumors; some inflammatory cytokines have been reported to have a regulatory role on the ENaC. The ENaC hyperfunction mediates the increase of intracellular Na+, and the elevated exchange of Na+ with Ca2+ leads to an intracellular calcium overload, which is an important mechanism for ENaC-related inflammation. Some of the research on the ENaC is controversial or unclear; we therefore reviewed the progress of studies on the role of ENaC-related inflammation in human diseases and their mechanisms.